Optimizing Multi-agent MicroGrid Resource Scheduling by Co-Evolutionary with Preference - Hongbin Sun; Tian Chunguang (Institute of Advanced Engineering and Science, 2013)
This paper presents a multi-agent framework for the control of distributed energy resources organized in Microgrids，which consists of integrated microgrids and lumped loads. Multiple objectives are considered for load balancing among the feeders, minimization of the operating cost, minimizing the emission, minimizing voltage profiles, minimizing active power losses. The agent represents message of microGrid unit and constitutes an autonomic unit. The network is achieved by the evolution of the agent based on the semantic negotiation. Based on the objectives evaluated by membership functions respectively, We propose a new Immune Co-Evolutionary Algorithm with Preference to solve it. Simulation results demonstrated that the proposed method is effective in improving performance and management of micro-sources. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3655